2-Methoxy-estradiol Loaded Alpha Lipoic Acid Nanoparticles Augment Cytotoxicity in MCF-7 Breast Cancer Cells. Issue 4 (7th December 2021) - Alhakamy, Nabil A.; Al-Rabia, Mohammed W.; Asfour, Hani Z.; Alshehri, Samah; Alharbi, Waleed S.; Halawani, Abdulrahman; Alamoudi, Abdulmohsin J.; Noor, Ahmad O.; Bannan, Douha F.; Fahmy, Usama A.; Kotta, Sabna
The therapeutic effectiveness of anticancer drugs with a selective target for the nucleus of cancer cells may be improved by experimental approaches. In this regard, the formulation of anticancer drugs is considered one of the best ways to improve their effectiveness in targeting cancerous tissues. To enhance the anticancer activity of 2-methoxy-estradiol (2 ME) for breast cancer, 2-methoxyestradiol loaded alpha lipoic acid nanoparticles have been formulated. The prepared formula was observed to be spherical with a nanometer-scale and low PDI size (.234). The entrapment efficiency of the 2ME-ALA NPs was 87.32 ± 2.21% with > 85% release of 2 ME within 24 h. There was a 1.2-fold increase in apoptosis and a 3.46-fold increase in necrosis of the MCF-7 cells when incubated with 2ME-ALA NPs when compared to control cells. This increased apoptosis was also associated with increased ROS and increased p53 expression in 2ME-ALA NPs treated cells compared to the raw-2 ME group. Evaluation of cell-cycle data showed a substantial arrest of the G2-M phase of the MCF-7 cells when incubated with 2ME-ALA NPs. At the same time, a dramatically increased number of pre-G1 cells showed the increased apoptotic potential of the 2 ME when administered via the proposed formulation. In the end, the differential upregulation of caspase-3, p53, and ROS in MCF-7 cells established the superiority of the 2ME-ALA-Ms approach in targeting breast cancer. In summary, these results demonstrate that 2ME-ALA NPs are an efficient delivery tool for controlling the growth of breast cancer cells.